Partikel Penegas Bahasa Indonesia dan Bahasa Arab: Kajian Analisis Kontrastif: A Contrastive Analysis - Wihandani Wihandani; Rohanda Rohanda; Yuliarti Mutiarsih (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
This study aims to analyze the morphological difficulty level of Arabic particles for Indonesian speakers through a contrastive analysis approach. The method used is a literature review with reference to Robert Lado's contrastive analysis theory and his six-level hierarchy of difficulty. The research data includes Indonesian and Arabic emphatic particles. The results of the analysis show four main morphological differences: (1) morphological position: Indonesian particles are generally postpositional, while Arabic particles are prepositional except for nūn al-tawkīd; (2) type of morpheme: Indonesian particles are mostly clitics except for pun, while Arabic particles are free morphemes except for nūn al-tawkīd and lām al-ibtidā'; (3) particle function: both function as emphatic particles, but the concept of ḥurūf al-qasam has no equivalent in Indonesian; (4) morphological variation: both are relatively invariant, although nūn al-tawkīd has phonological variations. A distinctive feature of Arabic is the use of more than one emphatic particle in a single word (e.g., lām al-ibtidā' and nūn al-tawkīd), which poses a unique cognitive challenge because Indonesian learners must process cumulative emphasis markers. Indonesian learners are not predicted to experience difficulties at level zero due to the similarity in basic functions. Difficulties arise at level three due to differences in morphological distribution, increase at level four due to features without equivalents such as ḥurūf al-qasam and variations of nūn al-tawkīd, and peak at level five due to the diversity of Arabic particle functions. This study provides a pedagogical framework for teaching Arabic emphatic particles with specific instructional strategies for each level of difficulty: positive transfer strategies for Level 0, explicit contrastive instruction for Level 3, intensive focus instruction with cultural-pragmatic explanations for Level 4, and systematic differentiation training for Level 5.